A built-in debugger for 1149.4 circuits - Manuel C. Felgueiras (2007)
Debugging mixed-signal circuits is usually seen as a complex task due to the presence of an analog part and the necessary interaction with a digital part. The use of debug and test tools that require physical access suffers from the same restrictions that led to other solutions based on electronic access, especially for digital circuits, due to the increasing operating frequencies and miniaturization scales. This is particularly the case that led to the emergence and wide acceptance of the IEEE1149 family of test infrastructures, which relies on an electronic test access port. While the IEEE1149.4 test infrastructure enables the structural and parametric test of mixed-signal boards, its use is still far from reaching a wide acceptance, namely due to the lack of alternative applications, such as debugging, as it is the case in the 1149.1 domain. This work describes a way to support debug operations in 1149.4 mixed-signal circuits, in particular a built-in condition detection mechanism able to support internal watchpoint/breakpoint operations.